Establishment and characterization of ovarian clear cell carcinoma patient-derived xenografts - Joseph J. Caumanns; Shang Li; Gert J. Meersma; Evelien W. Duiker; Ate G. J. van der Zee; G. Bea A. Wisman; Steven de Jong (Scientific Reports)
Abstract Interest in understanding the high chemoresistance and poor prognosis of advanced ovarian clear cell carcinoma (OCCC) is rising. Patient-derived xenografts (PDX) are widely used in vivo models because of their supposedly accurate morphologic and (epi)genetic representation of patient tumors. Here, we established five subcutaneous OCCC PDXs. The PDX.F1 engraftment success rate was over 30% with similar latency time and growth speed of PDX.F2. ARID1A, PTEN, ATM, BRCA1 and PIK3CA mutations were found in matched tumors and PDXs. ARID1A protein loss was further verified by immunohistochemical staining. Cyclophilin A staining depicted the replacement of human stroma by mouse stroma in PDX.F2, while PAS/PAS-D staining confirmed cellular glycogen accumulation in OCCC tumors and PDXs. SNP array and Infinium MethylationEPIC BeadChip array data analysis demonstrated the copy number alterations and DNA methylation signatures of genome-wide and tumor-driver genes in PDXs generally resembled their patients’ tumors. Promoter CpG islands of a small number of genes, enriched in PRC2/histone methylation related gene-sets, gained methylation (△β-value > 0.4) in PDXs vs patient tumors. In conclusion, the high phenotypic and molecular similarity allows the established PDXs to serve as potential preclinical models for future translational research of OCCC.